The Effect of Zig-Zag Training Method on the Dribble Skill of SSB Satria Muda - Adji Dwi Rogo; Wawan Syafutra; Muhammad Supriyadi (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine how much influence zigzag training has on dribbling skills in soccer games at SSB Satria Muda. This research is an experimental study using a pretest-posttest control design with zig-zag training as the independent variable, the dependent variable being dribbling skills. The subjects in this study were Ssb Satria Muda athletes, athletes selected using the proportional stratified random sampling technique. The data collection method is a test. In each group, the test was given at the beginning before the treatment and at the end after the treatment. The treatment given to the experimental group was in the form of zig-zag exercise, after being given exercise for 4 weeks with a frequency of exercise 3 times a week. Based on data analysis by statistical t-test with a significant level of = 0.05, t_count = 5,500 and t_table = 2,048, if t_count > t_table then Ha is accepted and Ho is rejected. Thus, the proposed Ha can be accepted as true, that zig-zag training has an effect on improving dribbling skills in soccer games at SSB Satria Muda. Keywords : Zigzag practice, Dribble skill in soccer game